1998
DOI: 10.1111/j.1600-051x.1998.tb02510.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the incidence of gingival abrasion as a result of toothbrushing

Abstract: The aims of the present study were: (1) to establish the incidence of gingival abrasion as a result of toothbrushing, using a manual and electric toothbrush; (2) to establish the influence of filament end-rounding on the incidence of gingival abrasion and the efficacy of toothbrushing; (3) to assess whether the speed of the electric brush has a feedback-effect on the brushing force used and to correlate the incidence of gingival abrasion with force. 2 experiments were carried out. In the first experiment, 50 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 15 publications
7
91
1
5
Order By: Relevance
“…In another study, with a crossover design in which panellists brushed their own teeth, the same conclusion was drawn 30. A comparable incidence of gingival abrasion for manual and power brushes was reported in a study with 50 participants who brushed for 3 weeks every other day with either a manual or power (oscillating–rotating) brush, before being assessed in a random split-mouth order 8. Another, 1-year longitudinal, study with 32 patients showed that over the long-term a power brush did not cause more abrasion than a manual brush 31.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In another study, with a crossover design in which panellists brushed their own teeth, the same conclusion was drawn 30. A comparable incidence of gingival abrasion for manual and power brushes was reported in a study with 50 participants who brushed for 3 weeks every other day with either a manual or power (oscillating–rotating) brush, before being assessed in a random split-mouth order 8. Another, 1-year longitudinal, study with 32 patients showed that over the long-term a power brush did not cause more abrasion than a manual brush 31.…”
Section: Discussionmentioning
confidence: 60%
“…Toothbrush grip 22, brushhead shape 23 and daily toothbrushing frequency 24 have all been thought to have an influence on gingival abrasion. It is generally accepted that stiffer filaments cause more gingival abrasion 25–27 and the need for end-rounded, rather than sharply-pointed, toothbrush filaments is well established 7,8,28. Although it is apparent that a number of factors can increase gingival abrasion, brushing force does not appear to be a factor 8 and there is even evidence that less force is used with a power brush than a manual brush 29.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that generic bristled tooth brushes can induce gingival abrasion [24], especially if the bristles are hard and not rounded [25,26]. This may occur even in those who use little force while brushing [27]. In our subjects, we asked them to return their used tooth brushes, and about 5 subjects surrendered the tooth brush they originally used prior to the study.…”
Section: Discussionmentioning
confidence: 99%
“…The examinations were performed by a single examiner (LC), who was calibrated to assess gingival abrasion 19 and stained plaque 20 (Turesky's modification of the Quigley-Hein Plaque Index; 20 Turesky et al 21 ). The evaluation of plaque and gingival abrasion included the use of a disclosing solution.…”
Section: Training and Calibrationmentioning
confidence: 99%